Effect of Salt Content on the Evaporation and Cracking of Soil from Heritage Structures - Kai Cui; Xiaozheng Zhao; Mingming Hu; Chen Yang; Guanchang Xie (Advances in Materials Science and Engineering)
The degree of damage to heritage structures in arid areas can be particularly serious due to long-term exposure to a harsh arid climate. In this paper, the characteristics of evaporation and cracking of soil taken from heritage structures with different NaCl concentrations are experimentally investigated by subjecting saturated soil samples taken from the Wang-Jing tower in Weihui City, Henan Province. Making soil sample of water content of 110% is used to test the rate of evaporation at a constant temperature and humidity, through which the changes in the evaporation rate, water content, fracture development, and fracture fractal dimension are obtained. The results show that, (1) with higher water content, NaCl can affect the evaporation process by increasing the matrix suction of the soil of the Wang-Jing tower and then affect the cracking process of soil. When 0%, 1%, 2%, and 4% NaCl are added, the residual water content of the samples is 3.15%, 4.23%, 4.82%, and 5.89%, respectively, which show an obvious trend of increasing water content; (2) the period with a stable fracture fractal dimension of the samples is shortened with an increase in NaCl concentration, and its maximum fractal dimension is reduced in turn; and (3) at a lower water content, NaCl crystallizes and precipitates in the pores of the soil, which provide a cementitious effect among the soil particles, thus inhibiting crack development.